Discovery of Selective Inhibitors of Endoplasmic Reticulum Aminopeptidase 1 - Maben, Zachary (J Med Chem, 2019)
ERAP1 is an endoplasmic reticulum-resident zinc aminopeptidase that plays an important role in the immune system by trimming peptides for loading onto major histocompatibility complex (MHC-I) proteins. Here we report discovery of the first inhibitors selective for ERAP1 over its paralogs ERAP2 and IRAP. Compound 1 (N-(N-(2-(1H-indol-3-yl)ethyl)carbamimidoyl)-2,5-difluorobenzenesulfonamide) and compound 2 (1-(1-(4-acetylpiperazine-1-carbonyl)cyclohexyl)-3-(p-tolyl)urea) are competitive inhibitors of ERAP1 aminopeptidase activity. Compound 3 (4-methoxy-3-(N-(2-(piperidin-1-yl)-5-(trifluoromethyl)phenyl)sulfamoyl)benzoic acid) allosterically activates ERAP1’s hydrolysis of fluorogenic and chromogenic amino acid substrates but competitively inhibits its activity towards a nonamer peptide representative of physiological substrates. Compounds 2 and 3 inhibit antigen presentation in a cellular assay. Compound 3 displays higher potency for an ERAP1 variant associated with increased risk of autoimmune disease. These inhibitors provide mechanistic insight into the determinants of specificity for ERAP1, ERAP2 and IRAP, and offer a new therapeutic approach of specifically inhibiting ERAP1 activity in vivo.